The Analysis of Transaction Costs and Revenue of Cayenne Pepper Farming: An Empirical Study in Semarang District - Sucihatiningsih Dian Wisika Prajanti; Etty Puji Lestari; Fauzul Adzim (Finance, Accounting and Business Analysis, 2022)
This study aims to analyze transaction costs and its effect on chili farming income in Semarang Regency. This study used a quantitative descriptive approach. The location of this study was in Semarang Regency. The population in this study were all cayenne pepper farmers in Semarang Regency, which amounted to about 1,345 people. The sampling technique in this study was simple random sampling with a total sample of 70 people. This study used two methods of data analysis, namely 1) analysis of transaction costs of cayenne pepper farming, 2) analysis of cayenne pepper farming income. The transaction costs of cayenne pepper farming consist of 4 (four) namely input procurement transaction costs, farming processing transaction costs (farming), output sales transaction costs, and transaction costs for supporting institutions. The highest transaction cost for Cayenne pepper farming is found in the Total Input Procurement Transaction Cost, which is Rp. 452,000 while the lowest is in the farming process of Rp. 197,000. The monitoring cost incurred by farmers is Rp. 45,000. The revenue of Cayenne pepper farming is Rp. 70,000,000/ha with the price of Rp. 35,000/kg. The use of pesticides to prevent pest and disease attacks. In Cayenne Pepper farming, the pesticides used by Cayenne pepper farmers are herbicides and insecticides. Herbicides are used to eradicate weeds and insecticides are used to eradicate pests. Pests that attack Cayenne pepper plants are red mites. The total pesticide cost incurred by farmers is Rp. 300,000/ha. The suggestion that can be given in this study is that the government needs to map and ensure the balance of supply and demand so that the price of cayenne pepper remains stable. It is necessary to conduct socialization with farmers when planting chilies so they do not lose money. There is a need for subsidies, especially for fertilizers, which have a very important role in increasing chili productivity.